Mulighetsrommet i kunstdidaktikken: betraktninger av til-stede-værelse - Gjærum, Rikke Gürgens (Nordic Journal of Art & Research, 2015)
The article explores Art Didactics as a room for possibilities for marginal voices. Through place philosophy the term “room” represents the metaphorical fulcrum in the article. The purpose is to open up an amazement community where we together walk the philosophical path from room to room in order to expand our understanding of both Marginality and Arts Didactics. The article contribute with a concept- and theory development concerning Art for, of and with people with marginal voices, seen through contemporary art examples from Disability Art represented by DE UTVALGTE and UNLIMITED 2014.